Bali Van Java Tourism Village Development Model Based on Local Wisdom in Patoman Village Banyuwangi - Mochamad Ardi Setyawan; Aditya Rachman (UNEJ e-Proceeding, 2021)
Patoman Village, Blimbingsari, Banyuwangi is known as Bali Van Java. This analysis takes an integrated and sustainable concept by involving the people of Patoman Village based on the idea of maintaining the existence of the local wisdom values of the Balinese people in Patoman Village 1) The concept of development based on Bali Van Java Local Wisdom is very relevant to be applied in Patoman Village, using the concept of integrated village development and integrated with the potential of the village, for example the potential of nature, culture and arts. 2) In order for the development of Patoman Bali Van Java Village based on local wisdom to develop properly, it needs to be supported by the facilities needed by the surrounding community. 3) There needs to be an integrated information center in Patoman Village as a place to carry out promotions related to the benefits of Patoman Village, both tourism and other potentials such as UMKM, and agricultural products 4) Patoman Village needs to be used as a model in managing culture so that conflicts do not occur but has an economic impact on society. 5) Environmental development needs to pay attention to local cranes in order to have aesthetic value and increase the attractiveness of tourists to visit. Keywords: Bali Van Java, Local Wisdom, Patoman Village, Tourism Village.